2021
DOI: 10.1111/cen.14626
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment does not to lead to insulin resistance nor excessive rise in IGF‐1 levels, while improving height in patients small for gestational age A long‐term observational study

Abstract: Objective In children born small for gestational age (SGA), the relationship between growth hormone (GH) treatment and insulin resistance (IR) has only been investigated for a short period, necessitating a longer observation period. This study aimed to evaluate the long‐term (10 years) effect of GH to SGA‐children on IR and safety during treatment. Design This was a multicenter observational study. Patients: SGA‐children who received GH treatment in Spain (stratified by Tanner‐stage and age at GH onset [two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our results for the whole observed group ΔHt12 SDS 0.57 and ΔHt24 SDS 0.38, as well as HV12 8.15 cm/year after the first and HV24 7.17 cm/year after the second year are consistent with the results obtained by Ranke et al or López-Siguero et al [ 16 , 17 ]. Both parameters indicate the benefit of treatment for SGA patients because they improve their centile position as well as maintain a relatively good HV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results for the whole observed group ΔHt12 SDS 0.57 and ΔHt24 SDS 0.38, as well as HV12 8.15 cm/year after the first and HV24 7.17 cm/year after the second year are consistent with the results obtained by Ranke et al or López-Siguero et al [ 16 , 17 ]. Both parameters indicate the benefit of treatment for SGA patients because they improve their centile position as well as maintain a relatively good HV.…”
Section: Discussionsupporting
confidence: 93%
“…The BA/CA ratio we obtained was comparable to those presented in the work of López-Siguero et al [ 17 ]. During the course of growth BA/CA ratio did not reach the value of 1.…”
Section: Discussionsupporting
confidence: 91%
“…Several national and international studies have investigated the effect of growth hormone (GH) treatment on height outcomes in children born SGA [10][11][12][13][14]. All of the studies carried out in children who were prepubertal at start of treatment showed a significant increase in stature with GH treatment, which was inversely proportional to the child's age at the start of treatment [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that individuals born SGA may have an increased risk of developing insulin resistance and metabolic syndrome in adulthood [8,16,17]. GH may temporarily reduce insulin sensitivity in these patients [18][19][20], although the only significant change appears to occur in the first year of treatment, with insulin resistance remaining within the normal range throughout longterm treatment [14]. Lastly, data concerning the effect of GH on bone maturation or the start of puberty are incomplete and contradictory [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Small for gestational age (SGA) fetuses or newborns are those that are smaller than average for their gestational age. This is typically indicated by a weight that is below the 10th percentile [ 82 , 83 ] and affects approximately 3–10% of live births [ 84 , 85 ]. Compared with infants born with a normal length and weight for gestational age, SGA is linked to cardiovascular disease, T2DM, increased risk for insulin resistance, and adults short stature [ 86 , 87 ].…”
Section: Effects Of the Flghr And D3ghr Isoforms On Various Growth Di...mentioning
confidence: 99%